Membrane-attached mammalian cytochromes P450: An overview of the membrane's effects on structure, drug binding, and interactions with redox partners - Šrejber, Martin; Navrátilová, Veronika; Paloncýová, Markéta; Bazgier, Václav; Berka, Karel; Anzenbacher, Pavel; Otyepka, Michal (Journal of inorganic biochemistry, 2018)
Mammalian cytochromes P450 are an important class of enzymes involved in the biotransformation of many endo- and exogenous compounds. Cytochrome P450 isoforms are attached to the membrane of the endoplasmic reticulum or mitochondria, and their catalytic domains move along the membrane surface while being partially immersed in the membrane environment. Their active sites are connected to both the membrane and cytosolic environments via a complex network of access channels. Consequently, they can accept substrates from both environments. The membrane also supports the interactions of cytochromes P450 with their redox partners. In this review, we provide an overview of current knowledge of the structure, flexibility, and interactions with substrates and redox partners of cytochrome P450 on membranes, amalgamating information derived from both experiments and simulations.
Keywords: Protein Binding; oxidace-redukce; vazba proteinů; Cell Membrane; systém (enzymů) cytochromů P-450; Animals; Oxidation-Reduction; lidé; Drug metabolism; Protein-membrane interactions; Cytochrome P-450 Enzyme System; Humans; zvířata; CYP; Ligand passage; buněčná membrána